2017
DOI: 10.1055/s-0043-121698
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenylated Phenolic Compounds from Morus macroura as Potent Tyrosinase Inhibitors

Abstract: Three new Diels-Alder adducts, macrourins E - G (1: -3: ), one new 2-arylbenzofuran, macrourin H (4: ), and eight known Diels-Alder adducts (5: -12: ) were isolated from . Their structures were elucidated through extensive analysis of spectroscopic data. TheH NMR and ECD trends in the determination of the configurations of these Diels-Alder adducts were summarized. The tyrosinase inhibitory activities of all compounds isolated were evaluated, and the new compounds (1: -4: ) as well as the eight known compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…For example, the most potent aurone, 4,6,4'-trihydroxyaurone induces 75% inhibition at 0.1 mM concentration and is highly effective compared to kojic acid 304 . In addition to synthetic compounds, several natural compounds such as (2'R)-2',3'-dihydro-2'-(1-hydroxy-1-methylethyl)-2,6'-bibenzofuran-6,4'-diol 305 and 2-arylbenzofurans isolated from Morus notabilis 306 and Morus yunnanensis 230 , benzofuran flavonoids such as mulberrofuran G (MG) and albanol B (AB) isolated from Morus sp 307 and macrourins E isolated from Morus macroura (IC 50 = 0.39 µM) are potent tyrosinase inhibitors among aurones 308 .…”
Section: Inhibitors From Natural Semisynthetic and Synthetic Sourcesmentioning
confidence: 99%
“…For example, the most potent aurone, 4,6,4'-trihydroxyaurone induces 75% inhibition at 0.1 mM concentration and is highly effective compared to kojic acid 304 . In addition to synthetic compounds, several natural compounds such as (2'R)-2',3'-dihydro-2'-(1-hydroxy-1-methylethyl)-2,6'-bibenzofuran-6,4'-diol 305 and 2-arylbenzofurans isolated from Morus notabilis 306 and Morus yunnanensis 230 , benzofuran flavonoids such as mulberrofuran G (MG) and albanol B (AB) isolated from Morus sp 307 and macrourins E isolated from Morus macroura (IC 50 = 0.39 µM) are potent tyrosinase inhibitors among aurones 308 .…”
Section: Inhibitors From Natural Semisynthetic and Synthetic Sourcesmentioning
confidence: 99%
“…Remarkably, it has been revealed that far IR irradiation can increase the TI activity of certain avonoid glycosides. [95][96][97][98][99][100][101][102][103] In a review of recent ndings, Orhan et al surveyed many tyrosinase inhibitors incorporating the avonoid scaffold. 104 Many promising TI's from different classes of natural and synthetic avonoids have been summarized and the role of avonoids has been highlighted and recommended as the focus of future and continued tyrosinase inhibition studies.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Previous bioactivity studies on kojic acid (1) revealed its antioxidant [18], tyrosinase inhibitory [19], anti-pigmentation (skin whitening) [20,21], nematicidal [22], antifungal [23] and antileishmanial [24] properties. Kojic acid (1) is a chelation agent produced by several species of fungi, especially Aspergillus oryzae, which has the Japanese common name koji.…”
Section: Discussionmentioning
confidence: 99%